Pemanfaatan Teknologi dalam Meningkatkan Komunikasi Bisnis UMKM Timah: Tinjauan Literatur atas Inovasi dan Tantangan - Mintawati, Hesri; Desianti, Lisa Chandrasari; Suhendar, Sundari; Martin Selian, Dwi Septiani; Sinta, Shindi Ayu (JUDICIOUS, 2025)
In today's digital era, the utilization of technology is key to improving business communication, especially for Micro, Small and Medium Enterprises (MSMEs) in the tin sector. This research aims to explore how technology can be used to improve business communication in tin MSMEs, as well as identify innovations and challenges faced. The research methodology involved a comprehensive literature review of relevant academic and practical sources. The results show that technologies such as social media, instant messaging applications, and online collaboration platforms have had a significant positive impact on the efficiency and effectiveness of business communication. However, there are several challenges to overcome, including limited resources, lack of digital literacy, and resistance to change. In conclusion, while technology offers many opportunities to improve tin MSME business communication, the right strategy and ongoing support are needed to overcome the challenges.